Recent Progress and Future Opportunities for Optical Manipulation in Halide Perovskite Photodetectors - Jiarui Zhang; Chi Ma (Nanomaterials)
Perovskite, as a promising class of photodetection material, demonstrates considerable potential in replacing conventional bulk light-detection materials such as silicon, III–V, or II–VI compound semiconductors and has been widely applied in various special light detection. Relying solely on the intrinsic photoelectric properties of perovskite gradually fails to meet the evolving requirements attributed to the escalating demand for low-cost, lightweight, flexible, and highly integrated photodetection. Direct manipulation of electrons and photons with differentiation of local electronic field through predesigned optical nanostructures is a promising strategy to reinforce the detectivity. This review provides a concise overview of the optical manipulation strategy in perovskite photodetector through various optical nanostructures, such as isolated metallic nanoparticles and continuous metallic gratings. Furthermore, the special light detection techniques involving more intricate nanostructure designs have been summarized and discussed. Reviewing these optical manipulation strategies could be beneficial to the next design of perovskite photodetector with high performance and special light recognition.